Disseminated herpes zoster infection initially presenting with abdominal pain in patients with lymphoma undergoing conventional chemotherapy: A report of three cases - Okuma, Hitomi Sumiyoshi (Oncol Lett, 2016)
Visceral disseminated varicella zoster virus (VZV) disease has a high mortality rate, and occurs in immunocompromised hosts, mostly subsequent to allogeneic stem cell transplantation. Only a few cases of this disease that onset during conventional chemotherapy in patients with lymphoma have been reported. The present study reports the cases of 3 patients with disseminated and visceral VZV infection undergoing treatment for follicular lymphoma, diffuse large B-cell lymphoma and peripheral T-cell lymphoma, not otherwise specified. All 3 patients presented with initial symptoms of abdominal pain, and 2 patients demonstrated syndrome of inappropriate antidiuretic hormone and hepatitis. All patients developed widespread cutaneous dissemination, and all had a low cluster of differentiation 4 cell count or lymphocyte count at the time of VZV diagnosis and at least 4 month prior. With intravenous systemic acyclovir therapy (Cases 1 and 3, 1500 mg/day; Case 2, 750 mg/day), the patients achieved complete recovery by day 14 of therapy. Visceral disseminated VZV infection is not limited to patients undergoing stem cell transplantation, and may present with abdominal pain with or without skin eruption. Visceral infection may take a poor clinical course, therefore, in patients with prolonged duration of low lymphocyte count and/or long-term use of steroids, the prophylactic use of acyclovir may be considered.